Cultivation of cells in alginate drops as a high-performance method of obtaining cell spheroids for bioprinting - S. Yu. Filippova; T. V. Chembarova; S. V. Timofeeva; I. V. Mezhevova; N. V. Gnennaya; I. A. Novikova; T. O. Lapteva (Южно-Российский онкологический журнал)
Purpose of the study. Testing the protocol of obtaining cell spheroids of breast cancer cell cultures for bioprinting by growing in alginate drops.Materials and methods. Cells of breast cancer cell lines BT-20 and MDA-MB-453 were cultured in DMEM medium supplemented with 10 % FBS. Next, the cells were removed from the plastic using a trypsin-V ersene solution and resuspended in a sterile 2 % alginate solution in DPBS to the concentration of 105 cells/ml. Then the alginate solution with the cells was slowly dripped through a 30G needle into a sterile cooled solution of calcium chloride (100 mM) from a height of 10 cm. After polymerization, alginate drops were washed in DMEM and cultured for two weeks in DMEM with the addition of 10 % FBS at 37 °C and 5.0 % CO2.The spheroids formed in the alginate were photographed on the 3rd, 7th, 10th, and 14th days of cultivation, after which they were removed from the alginate by keeping in 55 mM sodium citrate solution with the addition of 20mM ethylenediaminetetraacetic acid (EDTA) and embedded in paraffin blocks according to the standard method, followed by histological examination.Results. Cellular spheroids were formed in both cell cultures already on the 3rd day of cultivation. From the 3rd to the 10th day in both cultures, a uniform growth of cell spheroids was observed with a gradual slowdown in the increase in the size of spheroids by the 14th day of cultivation. On the 10th day the proportion of cells that formed clones (more than 500 μm2 in size) was 25.2 % ± 7.1 % (n = 25) in the BT-20 culture and 38.5 % ± 9.9 % (n = 25) in MDA-MB-453 culture. On the 14th day, BT-20 culture was characterized by spheroids varying little in size and shape, with an average area of 1652 ± 175 µm2, having a dense structure with smooth edges. The spheroids in MDA-MB-453 culture turned out to be more loose and easily deformed, their size and shape varied noticeably, the average area of the spheroids was 2785 ± 345 µm2.Conclusion. The production of spheroids in alginate drops is inferior in speed to the methods of forming cell conglomerates in hanging drops or on microwells, but it surpasses these methods in productivity, which is comparable to the production of spheroids by constant medium stirring on low-adhesive substrates. In addition, the clonal nature of the obtained spheroids leads to an increase in research costs and thus limits their scalability.